Plastic - Guild, Scott (Pantheon Books, 2024)
"For fans of Interior Chinatown and American War, a surreal, hilarious, and sneakily profound debut novel that casts our current climate of gun violence and environmental destruction in a surprising new mold. Erin is a plastic girl living in a plastic world. Every day she eats a breakfast of boiled chicken, then coveys her articulated body to Tablet Town, where she sells other figurines Smartbodies: wearable tech that allows full, physical immersion in a virtual world, a refuge from real life's nuclear wars, oppressive governmental monitoring, and omnipresent eco-terrorist insurgency. If you cut her, she will not bleed - but she and her fellow figurines can still be cracked or blown apart by gunfire or bombs, or crumble away from nuclear fallout. Erin, who's lost her father, sister, and the love of her life, certainly knows plenty about death. An attack at her place of work brings Erin another too-intimate experience, but it also brings her Jacob: a blind figurine whom she comforts in the aftermath, and with whom she feels an almost instant connection. For the first time in years, Erin begins to experience hope - hope that until now she's only gleaned from watching her favorite TV show, the surrealist retro sitcom "Nuclear Family." Exploring the wild wonders of the virtual reality landscape together, it seems that possibly, slowly, Erin and Jacob may have a chance at healing from their trauma. But then secrets from Erin's family's past begin to invade her carefully constructed reality, and cracks in the facade she's constructed around her life threaten to reveal everything vulnerable beneath. Both a crypto-comedic dystopian fantasy and a deadly serious dissection of our own farcical pre-apocalypse, Scott Guild's debut novel is an achingly beautiful, disarmingly welcoming, and fabulously inventive look at the hollow core of modern American society-and a guide to how we might reanimate all its broken plastic pieces"--